Early mortality and complications associated with catheter ablation of atrial fibrillation: analysis of the entire procedure in Korea from 2007 to 2016. (24th May 2021) - Yang, PS; Byun, JH; Sung, JH; Joung, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: There is limited data regarding the early mortality and adverse outcomes from catheter ablation of atrial fibrillation (AF) in Korea. The aim of this study was to examine the early mortality and frequency of adverse outcomes associated with AF catheter ablation from 2006 to 2016 in Korea. Methods: From 2006 to 2016 in the Korean National Health Insurance Service database, 11, 893 individuals underwent catheter ablation for AF. We investigated the frequency of complications and early mortality associated with AF ablation and comorbidities that led to adverse outcomes after AF ablation. Results: Out of all 11, 893 procedures, early mortality occurred in 38 cases (0.32%). Annual trends in AF procedural complications occurring during index admission for AF ablation decreased from 9.25% in 2006 to 6.49% in 2016 (P for trend = 0.004). The early mortality rate after AF ablation had remained unchanged between 2006 and 2016. After adjustment for age, comorbidities, and medication, procedural complications (adjusted odds ratio[aOR]: 16.1; P < 0.001), age (aOR: 1.25; P = 0.024), history of hemorrhagic stroke (aOR: 4.74; P = 0.019), and less experience with AF ablation of the hospital (aOR: 2.85; P = 0.024) were associated with early mortality. Among procedural complications, atrioesophageal fistula (aOR: 199.8; P < 0.001), access site complications (aOR: 6.08; P = 0.005), complete heart block (aOR: 11.3; P = 0.029), pneumothorax (aOR: 62.0; P < 0.001), and procedure related pneumonia (aOR: 39.0; P < 0.001) were associated with early mortality. Conclusions: Procedural complications, history of hemorrhagic stroke, and less experience with AF ablation of the hospital were predictors of early mortality. Out of all complications, atrioesophageal fistual, procedure related pneumonia, and in-hospital stroke were related to early mortality. Adequate management of complications may contribute to reducing the number of early mortalty rates following AF ablation.